A New Paradigm for Water Resource Governance in Indonesia : Reflecting on Constitutional Court Decision Number 85/PUU-XI/2013 Through the Narrative of Jasser Auda's Maqashid Syariah - Tohari, Ilham; Rohman, Baitur; Toriqirrama, Faby (Department of Constitutional Law, Faculty Sharia and Law, UIN Sunan Ampel Surabaya, 2025)
This study examines water resource management in Indonesia following the annulment of the Water Resources Law by Constitutional Court Decision No. 85/PUU-XI/2013, which mandated that water governance prioritize the greatest prosperity of the people. Despite the subsequent enactment of Law No. 17/2019, persistent issues of corporate industrialization, exploitation, and privatization of water sources threaten citizens' fundamental right to water and ecological sustainability. The paper adopts Jasser Auda’s contemporary Maqashid al-Shariah with its system approach as an alternative analytical framework. Auda's methodology shifts the maqasid focus from classical preservation to construction, development, and the fulfillment of human rights (hifdz al-huquq al-insan), employing six interconnected features, including a hierarchical structure. The analysis explicitly places the fulfillment of the people's rights to water within Auda's General Maqasid (Maqasid al-‘Ammah). This classification underscores the urgent need for water access as a fundamental human necessity, requiring a social and public dimension of governance that transcends individual interests.